A correlation between severity of chronic obstructive pulmonary disorders, electrocardiography and echocardiography of patients: a prospective observational study - Krishna Appaji, C. Sri; Ravinder, P. (International Journal of Advances in Medicine, 2020)
Background: Chronic obstructive pulmonary disease (COPD) is defined as a disease state characterised by persistent respiratory symptom and airflow limitation which is not fully reversible. It has been reported that patient with COPD has higher mortality due to cardiac disorder. We have designed this study with an aim to evaluate electrocardiography and echocardiography changes in COPD patients and correlate this finding with severity of disease. Method: In present study 60 randomly selected COPD patients were evaluated clinically, echocardiographically, electrocardiographically and pulmonary function test was performed. A careful history of patient was taken regarding demography, symptoms and aggravation factors. Detailed clinical examination of patient was done to know the sign symptom of cardiological and respiratory involvement. Result: In patients with severe COPD 4 (20%) patients have normal ECG, 12 (60%) have P pulmonale, 14 (70%) patients have right ventricular hypertrophy, low voltage complex was found in 6 (30%), RBBB was present in 4 (20%) patients, 12 (60%) have r wave in their electrocardiograph (ECG) and 2 (10%) patients presented with arrhythmia. Conclusions: From our study we can conclude that most of the patients with COPD were in 5th and 6th decade of life with male predominance. Patients with moderate airflow obstruction were common than severe obstruction. Cardiovascular changes depend upon the severity of disease.